Stress-Corrosion Cracking : Materials Performance and Evaluation - Jones, Russell H. (Ohio: ASM International, 1992)
Contents Complete coverage of SCC for a variety of materials and SCC in different carbon and low-alloy steels high-strength steels stainless steels nickel-base alloys copper alloys aluminum alloys magnesium alloys titanium alloys zirconium alloys uranium alloys amorphous alloys glasses and ceramics weldments in boiling water reactor service.
Keywords: Stress corrosion; Alloys -- Stress corrosion